A pilot study of the challenges and prospects of continous assessment implementation in Nigeria (2009)
This study obtained basic information from teachers and students on the challenges and prospects of implementation continous assessment in the Nigerian school system. Secondary schools in Ilorin, the capitalcity of Kwara state, located in the central region of Nigeria were sampled for use in the study. It employed survey research design executed through the collection of ex post facto data. Two hundred and forty respondents comprising one hundred and twenty teachers and one hundred and twenty students were respectively sampled and used as subjects in the study. Two questionnaire, one for teachers and one four students, were developed and used to collect data which were analyzed using mainly percentages. Findings show that the greatest challenges of implementating CA in Nigerian secondary schools include poor level of preparedness for tests on the part of the students, poor test administration procedures, poor handling of scores anf feedback to students, poor coverage of instructional contents by test contents, large classes, inadequate time for test and lack of knowledge and skills of the appropriate evaluation techniques. Respondents suggested that time should be given to implementing CA, teachers should be adequatly trained in the techniques of evaluation, relevant modern technology for its conduct and recording should be provided for teachers. It was discovered that Nigerian know that CA possesses some prospects if properly implemented. These include reducing examination malpractices, engendering quality study habit in the student, improving educational and learning outcomes attainment among others. It was thus recommended that teachers should be given relevant training on modern evaluation techniques and schools provided the enabling enviroment for CA to work.